Viana Do Castelo: Stucco Art and Artists - Moura, Anabela; Moreira, Raquel (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2021)
This project describes an Art Project carried out at the Higher School of Education of Viana do Castelo Polytechnic Institute, Northern Portugal, in a class of the 2nd year of the Basic Education course within the curriculum unit "Artistic and Cultural Animation Techniques" in the academic year 2020/2021. The main aim of this article is to disseminate a project that combines cultural and artistic animation with the promotion of cultural heritage and, in particular, with the valorization of an artistic tradition from Alto Minho that tends to disappear – the stucco art. Methodologically, the action research method was used in combination with the service-learning model, using the interview as a research technique to collect data on the problems that affect this hiddenstream art form. A number of games were developed to address the art of stucco for 1st cycle primary education children, as well as a video recording on the history of stucco. The imaginative and innovative responses of the university students help to highlight the need for the protection and appreciation of such a tradition in the general population and among 1st cycle children.